Management of production and economic growth of the micro enterprise of textile production in Riobamba–Ecuador - Paredes Gavilanez, Jorge Gualberto (2018)
Objective: To determine the existing synergy between production management and economic growth of textile production establishments in Riobamba, 2017 period. Method: It is a descriptive, non-experimental correlational research and the direct actors are micro entrepreneurs dedicated to the textile activity, many of them professionals in other areas of knowledge, but who have ventured into this activity. The literature regarding "production management and economic growth" was reviewed, which allowed to objectively identify characteristics of daily practice. Results: a survey was applied; the data was processed using the system (SPSS Version 23 for Windows). The "data processing" was carried out applying the Pearson correlation analysis assigning a level of significance of 0,05 to determine the level of association between the variables considered. The result showed that the variables management of production and economic growth are not independent; they are correlated. Conclusions: An intelligent surmise is presented where the problem is approached objectively and the imminent need to design and implement strategies to strengthen production management processes is established. Since productivity and economic growth are in synergy and constitute a key support for textile production companies.